Interfaz academia–políticas públicas: experiencias interdisciplinarias en alimentación y nutrición en Uruguay desde un enfoque crítico - Gastón Ares; Alejandra Girona (INTER DISCIPLINA, 2026)
Addressing the multiple challenges humanity faces in the field of food and nutrition requires strengthening the interface between academia and public policy. Achieving this objective is particularly complex, given the diversity of actors, timelines, and languages involved. Therefore, analyzing successful experiences becomes essential to identify mechanisms, conditions, and strategies that foster the development of strong and sustainable links between academic knowledge production and the processes of public policy design and implementation. Within this framework, this paper aims to analyze experiences of interaction between academia and public policy through a case study of the Interdisciplinary Center on Food and Wellbeing at the Universidad de la República (Uruguay). The collaboration between this collective and public institutions in the field of food and nutrition has taken multiple forms, which can be grouped into two main categories: external advisory schemes and internal advisory schemes. The analysis of these experiences makes it possible to identify several factors that have facilitated the strengthening of the science-policy interface, including the development of trust-based relationships, the relevance of the knowledge produced, and its effective translation into clear and accessible language. At the same time, the experiences reviewed highlight the need to move toward the consolidation of stable institutional structures, the availability of dedicated funding, and the academic recognition of interdisciplinary work as necessary conditions for contributing to the development of more effective, equitable, and sustainable food policies.